The Extent and Consequences of Teacher Biases against Immigrants - Ellen Sahlström; Mikko Silliman (Center for Economic Studies and ifo Institute (CESifo), 2024)
We study the extent and consequences of biases against immigrants exhibited by high school teachers in Finland. Compared to native students, immigrant students receive 0.06 standard deviation units lower scores from teachers than from blind graders. This effect is almost entirely driven by grading penalties incurred by high-performing immigrant students and is largest in subjects where teachers have more discretion in grading. While teacher-assigned grades on the matriculation exam are not used for tertiary enrollment decisions, we show that immigrant students who attend schools with biased teachers are less likely to continue to higher education.
Keywords: I24; J15; J68; 330; immigrants; discrimination; teachers; education policy